Enhancing community development for low-income vertical housing in Davao City through applied placemaking and spatial identity - Zarate, Justine Karl V. (2023)
Vertical housing is one of the key factors for urban growth in Davao City, as these answers the rapidly rising population and affordable living spaces in a diverse demographic within the urban landscape. This research explores placemaking in vertical housing that comes from identifying the prevailing public spaces and recognizing the residents' imageability on public spaces through a sense of place and their experiences. In order to find out the current norms and interest of vertical housing residents in Davao City, the data gathering process utilizes key informant interviews with the property mangers of each study area and a focus group discussion with the homeowner's association. The results gained from the data gathering concludes that social spaces of vertical housing residents prioritize green spaces, as well as accommodation for leisure in activities and relaxation, and small enclosed spaces for community gathering. The results of the study aim to establish a design guideline that produces a place for community development by community-built spaces through prevailing places and perceived imageability, envisioning future developments for vertical housing in Davao City without compromising outside factors such as community parks and open spaces, thus allowing a uniqueness in design features towards common spaces within vertical housing.